The variable-mass seepage law of broken porous rock: an experimental study - Yingchao Wang; Fan Chen; XiaoZhao Li; Xin Yin; Yating Lei (Geomatics, Natural Hazards & Risk, 2020)
Induced by tunnel excavation, the particles constantly shift in broken porous rock of faults until failure occurs, which provides channels for water inrush. Therefore, it is essential to investigate the particle migration of broken porous rock. Thus, a visual experimental system of particle migration was developed independently. Further study on the mass loss evolution of broken porous rock induced by seepage failure was performed using physical model tests, and the effect of the grain gradation of broken porous rock was also analyzed. According to the composition and lost characteristics of the samples, the samples were divided into dense-suspension structure and void-skeleton structure. The results indicated that the mass loss of the particles decreased with the increase in the gradation coefficient when the sample had a dense-suspension structure, while there was no significant change in the lost quality with the increase of gradation coefficient when the sample had a void-skeleton structure. Moreover, the time required for water inrush decreased with the increase in the gradation coefficient, which is because the higher the content of the fine particles is, the lower the permeability of the sample. Sample settlement is positively correlated with the lost quality of particles.